Reducing ammonia volatilization in rice paddy: the importance of lower fertilizer rates and soil incorporation - Canatoy, Ronley C.; Cho, Song Rae; Galgo, Snowie Jane C.; Kim, Pil Joo; Kim, Gil Won (Frontiers in Environmental Science, 2024)
In rice paddies, which exhibit higher ammonia (NH₃) emission factors than upland soils, identifying key drivers of NH₃ flux intensity is crucial. Contrary to the commonly held view that NH₃ flux is primarily governed by soil ammonium (NH₄⁺) concentrations, we found no significant relationship between NH₃ flux and NH₄⁺ levels in the soil during rice cultivation. To pinpoint a primary factor influencing NH₃ flux intensity under conventional rice cropping practices, we conducted a 2-year field study applying four nitrogen (N) fertilization rates (0, 45, 90, and 180 kg N ha⁻¹) using urea [(NH₂)₂CO], the most common N fertilizer. NH₃ emissions were tracked using the ventilation method. Following N application, NH₃ flux sharply increased but rapidly returned to baseline. Half of the N applied as a basal fertilizer was incorporated within the soil, contributing only 10% of total NH₃ emissions. In contrast, top-dressed applications—20% of total N at the tillering stage and 30% at panicle initiation—accounted for approximately 90% of NH₃ loss. Seasonal NH₃ flux increased quadratically with rising N application rates, correlating strongly with NH₄⁺ concentrations in floodwater rather than soil. Grain yield responded quadratically to N levels, peaking at 120 kg N ha⁻¹ with a 37% increase over control yields. NH₃ flux intensity, defined as seasonal NH₃ flux per unit of grain yield, showed a quadratic response to N fertilization, decreasing with initial fertilizer additions (up to 38 kg N ha⁻¹) but then sharply increased with further N fertilization increase. Hence, reducing NH₄⁺ concentrations in floodwater through moderated N application and deeper fertilizer placement could be essential for minimizing NH₃ volatilization in rice systems.